1992
DOI: 10.3109/00498259209051869
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of mechanisms of reactive metabolite formation from (R)-(+)-pulegone

Abstract: 1. (R)-(+)-Pulegone is a monoterpene that is oxidized by cytochromes P-450 to reactive metabolites that initiate events in the pathogenesis of hepatotoxicity in mice, rats and humans. 2. Selective labelling of (R)-(+)-pulegone with deuterium revealed that menthofuran was a proximate hepatotoxic metabolite formed by oxidation of the allylic methyl groups of pulegone. Incubations of pulegone with mouse liver microsomes in an atmosphere of 18O2 resulted in the formation of menthofuran that contained only oxygen-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…A dose-response study showed that deuterium substitution for hydrogen in the allylic methyl groups decreased the extent of hepatocellular injury in mice by 2-to 3-fold (Gordon et al, 1987). An intrinsic deuterium isotope effect was observed in vitro for oxidation (k H /k D ϳ7-8) of the allylic methyl groups of pulegone to an E-allylic alcohol and menthofuran, which arises from intramolecular cyclization of a Z-allylic alcohol and subsequent dehydration (Table 4 from Nelson et al, 1992). Isotopically sensitive branching of the metabolism of pulegone to other oxidation products also occurs (Nelson et al, 1992).…”
Section: Use Of Deuterium Isotope Effects To Probe P450 Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A dose-response study showed that deuterium substitution for hydrogen in the allylic methyl groups decreased the extent of hepatocellular injury in mice by 2-to 3-fold (Gordon et al, 1987). An intrinsic deuterium isotope effect was observed in vitro for oxidation (k H /k D ϳ7-8) of the allylic methyl groups of pulegone to an E-allylic alcohol and menthofuran, which arises from intramolecular cyclization of a Z-allylic alcohol and subsequent dehydration (Table 4 from Nelson et al, 1992). Isotopically sensitive branching of the metabolism of pulegone to other oxidation products also occurs (Nelson et al, 1992).…”
Section: Use Of Deuterium Isotope Effects To Probe P450 Reactionsmentioning
confidence: 99%
“…An intrinsic deuterium isotope effect was observed in vitro for oxidation (k H /k D ϳ7-8) of the allylic methyl groups of pulegone to an E-allylic alcohol and menthofuran, which arises from intramolecular cyclization of a Z-allylic alcohol and subsequent dehydration (Table 4 from Nelson et al, 1992). Isotopically sensitive branching of the metabolism of pulegone to other oxidation products also occurs (Nelson et al, 1992). The relatively low isotope effect observed for pulegone-d 3 appears to reflect the ability of the isopropylidene group to topomerize within the cytochrome P450 active site after initial hydrogen atom abstraction (McClanahan et al, 1988).…”
Section: Use Of Deuterium Isotope Effects To Probe P450 Reactionsmentioning
confidence: 99%
“…18,19 Biosynthesis of 3 and 4 from pulegone via 11 has been shown to occur in mouse and human liver, 20,21 in which the oxidation is performed by cytochrome P-450s, as shown in Scheme 7. Considering this, we propose a similar biochemical pathway in peppermint species, where 1 would be on the pathway from 11 to 3.…”
Section: Identification Of Menthofurolactone 1 In Mintmentioning
confidence: 99%
“…The possible formation of the ketoenal via a pathway involving 2-hydroxy-(R)-(+)-menthofuran also is indicated and this compound has been isolated after incubation of (R)-(+)-menthofuran with human cytochrome P450s. Further evidence for this pathway is provided by the isolation both in vivo and in vitro of (+)-mintlactone and (-)-isomintlactone, which are rearrangement products of 2-hydroxy(R)-(+)-menthofuran (Nelson et al, 1992a;Thomassen et al,1992;Khojasteh-Bakht et al,1999).…”
Section: Hazard Identification/characterisationmentioning
confidence: 99%